Financial Literacy around the World: What We Can Learn from the National Strategies and Contexts of the Top Ten Most Financially Literate Nations. Issue 1 (3rd April 2022) - Faulkner, Ash
ABSTRACT: Despite the fact that the United States is one of the wealthiest nations in the world, it is not among the most financially literate. Individuals in the U.S., on average, have relatively large amounts of money about which they must make decisions, but they do not have commensurate levels of financial literacy. This research explores the financial literacy contexts and national strategies at play in the most financially literate nations in the world: Australia, Canada, Finland, Germany, Israel, the Netherlands, Sweden, and the United Kingdom. This article utilizes content analysis to explore the existing scholarly literature, national financial literacy strategies, and associated policy literature in these highly literate nations. This research will provide librarians in the U.S. with a broader context, both internationally and beyond library science literature, through which to view our own financial literacy participation, and to consider ways in which the financial literacy efforts at play in these other nations may provide us with ideas to expand or alter our efforts on national, local, and individual levels. Librarians in other nations may also benefit from this international view of financial literacy and be able to apply new concepts or ideas to their own financial education efforts.